(untitled) (Journal of Health, Population and Nutrition, 2012)
Plasmodium vivax is traditionally known to cause benign tertian malaria, although recent reports suggest that P. vivax can also cause severe life-threatening disease analogous to severe infection due to P. falciparum. There are limited published data on the clinical and epidemiological profiles of children suffering from severe malaria in an urban setting of India. To assess the clinical and epidemiological profiles of children with severe malaria, a prospective study was carried out during June 2008December 2008 in the Department of Pediatrics, Guru Teg Bahadur Hospital, a tertiary hospital located in East Delhi, India. Data on children aged ?12 years, diagnosed with severe malaria, were analyzed for their demographic, clinical and laboratory parameters. All patients were categorized and treated as per the guidelines of the World Health Organization. In total, 1,680 children were screened for malaria at the paediatric outpatient and casualty facilities of the hospital. Thirty-eight children tested positive for malaria on peripheral smear examination (2.26% slide positivity rate). Of these, 27 (71%) were admitted and categorized as severe malaria as per the definition of the WHO while another 11 (29%) received treatment on outpatient basis. Most (24/27;88.8%) cases of severe malaria (n=27) were infected with P. vivax. Among the cases of severe malaria caused by Plasmodium vivax (n=24), 12 (50%) presented with altered sensorium (cerebral malaria), seven (29.1%)had severe anaemia (haemoglobin <5 g/dL), and 17 (70.8%) had thrombocytopaenia, of which two had spontaneous bleeding (epistaxis). Cases of severe vivax malaria are clinically indistinguishable from severe falciparum malaria. Our study demonstrated that majority (88.8%) of severe malaria cases in children from Delhi and adjoining districts of Uttar Pradesh were due to P. vivax-associated infection. P. vivax should, thus, be regarded as an important causative agent for severe malaria in children. DOI: http://dx.doi.org/10.3329/jhpn.v30i1.11291 J HEALTH POPUL NUTR 2012 Mar;30(1):113-116